Right to Health and the Human Organ: Right as a Consequence? - Sandor, Judit (Pravni zapisi, 2014)
In the field of health care, right to health care requires a progressive interpretation whenever a new medical technology promises the preservation of life and health. Progressive interpretation takes into account both the legal and the technological development and though gradually but it enhances and specifies the scope of the rights vis-à-vis the treatments that have become part of the mainstream. The field of transplantation makes it possible to study all classical and new elements of right to health. The European approach, which categorically bans the payment for organs but relies on an opting out system in the case of cadaver donation, created a new public domain in which right to health and right to health care have become essential in the field of transplantation. People on the waiting list for organs evidently have a right to health. But this right does not provide direct entitlement to any particular human organ but it includes access to adequate health care and information with respect to organ donation. Furthermore, fair allocation of available organs, equity, access to postoperative treatment for both the donor and for the recipient are involved in a general right to health. The problem, however, as we have seen, is that the most important element of their health care: the availability of a viable organ depends on the altruism of others. The legal system, and more specifically the constitutional framework, cannot grant access to human organs as part of the basic rights.